A multidirectional two-tube method for chemical pleurodesis could improve distribution of the sclerosing agent within the pleural cavity – A pilot study. (August 2021) - Campion, Eoin; Mallah, Saad I.; Azhar, Maimoona; O'Keeffe, Dara; Hameed, Aamir
Abstract: Introduction: Malignant pleural effusion (MPE) affects approximately 200, 000 people in the United States per annum. Chemical pleurodesis is a recommended first line treatment in the management of MPE, however, success rates as low as 43% has been reported. A bedside chemical pleurodesis can cost up to 11, 224 and an estimated inpatient annual expenditure of more than 5 billion in the US alone. This study aims to assess the distribution of the talc slurry within the pleural space using human cadaveric models and to determine the force required to push the talc slurry though a 14 Fr chest tube. Materials and methods: The force required to administer the talc slurry through a 14 Fr chest tube was tested using a Zwick/Roelle Z005 mechanical tester, using a porcine thoracic biomodel. Talc slurry distribution within the pleural cavity was assessed by direct visualisation following administration to the human cadaveric models using single and multidirectional two-tube methods. Results: Maximum force required to push the talc slurry through a 14 Fr chest tube was 11.36 N ± 2.79 N. Distribution of the talc slurry within the pleural cavity was found to be poor with a single tube method. Multidirectional two-tube method of administration showed more even distribution. Conclusion: The experimental multidirectional two-tube method results in wider distribution of the talc slurry within the pleural cavity and could further improve success rate of the talc pleurodesis. Highlights: Yearly, there are over 150, 000 new cases of MPE in the US alone. Success rate of talc pleurodesis as low as 43% has been reported. Doctor's hand grip strength does not affect the talc distribution within the pleural cavity. Bedside multidirectional two-tube method may improve the success rate of talc slurry pleurodesis.